1998
DOI: 10.1175/1520-0493(1998)126<0303:tsaeoa>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

The Structure and Evolution of a Continental Winter Cyclone. Part I: Frontal Structure and the Occlusion Process

Abstract: The production of a narrow, heavy, occasionally convective snowband that fell within a modest surface cyclone on 19 January 1995 is examined using gridded model output from a successful numerical simulation performed using the University of Wisconsin-Nonhydrostatic Modeling System. It is found that the snowband was produced by a thermally direct vertical circulation forced by significant lower-tropospheric warm frontogenesis in the presence of across-front effective static stability differences as measured in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
71
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(77 citation statements)
references
References 43 publications
6
71
0
Order By: Relevance
“…Petterssen frontogenesis has been used previously to diagnose fronts in the central United States (e.g., Koch 1984;Keshishian et al 1994;Martin 1998a;Schultz 2004), the western United States (Steenburgh and Mass 1994;Schultz and Knox 2007;Steenburgh et al 2009;Schumacher et al 2010;West and Steenburgh 2010), and idealized baroclinic waves (Sch€ ar and Wernli 1993;Schultz and Zhang 2007); to calculate climatologies of frontogenesis (Satyamurty and De Mattos 1989); to determine regions of ascent associated with precipitation bands within heavy rainstorms (Sanders 2000) and within snowstorms (e.g., Bosart and Lin 1984;Keshishian and Bosart 1987;Roebber et al 1994;Martin 1998b;Trapp et al 2001;Novak et al 2004Novak et al , 2006Novak et al , 2008Novak et al , 2009Novak et al , 2010; to determine the time of extratropical transition of a tropical cyclone (Harr and Elsberry 2000); and to indicate regions of predecessor precipitation ahead of tropical cyclones (e.g., Galarneau et al 2010;Moore et al 2013). Lackmann (2011, sections 6.2 and 6.3) provides a moredetailed description of Petterssen frontogenesis.…”
Section: Petterssenmentioning
confidence: 99%
“…Petterssen frontogenesis has been used previously to diagnose fronts in the central United States (e.g., Koch 1984;Keshishian et al 1994;Martin 1998a;Schultz 2004), the western United States (Steenburgh and Mass 1994;Schultz and Knox 2007;Steenburgh et al 2009;Schumacher et al 2010;West and Steenburgh 2010), and idealized baroclinic waves (Sch€ ar and Wernli 1993;Schultz and Zhang 2007); to calculate climatologies of frontogenesis (Satyamurty and De Mattos 1989); to determine regions of ascent associated with precipitation bands within heavy rainstorms (Sanders 2000) and within snowstorms (e.g., Bosart and Lin 1984;Keshishian and Bosart 1987;Roebber et al 1994;Martin 1998b;Trapp et al 2001;Novak et al 2004Novak et al , 2006Novak et al , 2008Novak et al , 2009Novak et al , 2010; to determine the time of extratropical transition of a tropical cyclone (Harr and Elsberry 2000); and to indicate regions of predecessor precipitation ahead of tropical cyclones (e.g., Galarneau et al 2010;Moore et al 2013). Lackmann (2011, sections 6.2 and 6.3) provides a moredetailed description of Petterssen frontogenesis.…”
Section: Petterssenmentioning
confidence: 99%
“…This lack of observed data, both in space and time, makes it difficult to assess the severity of conditions on Lake Superior throughout the storm, and how those conditions varied. Numerous studies (Uccellini et al 1987;Whitaker et al 1988;Martin 1998a;Mann et al 2002;Roebber et al 2002;Poulos et al 2002;Meyers et al 2003) have shown the utility of using numerical weather prediction models to better diagnose the specific conditions of the atmosphere throughout an event. It was therefore determined that high-resolution numerical simulations could be used to help attain a more complete picture of the wind and wave conditions during the storm.…”
Section: Filling the Gapsmentioning
confidence: 99%
“…Previous studies that included successful model simulations of events (Martin 1998b;Roebber et al 2002;Poulos et al 2002;Meyers et al 2003) utilized high-resolution output from the simulations to help diagnose conditions in greater detail than would be possible through observational data alone. Following along these lines, we believe that if the atmospheric simulation successfully resolves synoptic-scale conditions, it also offers a reasonable estimate of mesoscale details over Lake Superior throughout the storm.…”
Section: Fig 4 Computational Domain and Associated Nests For The Ramentioning
confidence: 99%
“…These two satellite imagery perspectives illustrate the juxtaposition of two critical airstreams that contributed to the heavy snowfall bands in South Dakota. The warm, moist airstream, known as the warm conveyor belt (WCB; Carlson 1980), rises as it moves cyclonically to the northwest, forming a trough of warm air aloft (trowal; Martin 1998). For this event, evidence of the trowal is seen as an axis of high equivalent potential temperature (q e ) wrapping into western Minnesota at 650 hPa at 1500 UTC (Fig.…”
Section: Band On the Runmentioning
confidence: 99%